Uterine carcinosarcoma with heterologous osseous elements: a case report of an extremely rare clinical occurrence with literature review - Al Dallal, Hiba A.; Jacobs, Taylor H.; Bergman, Cody L.; Narayanan, Siddharth; Kaur, Arshi; Al-Quran, Samer Z.; Chopra, Harpreet Kaur (Frontiers in Oncology, 2025)
Carcinosarcoma is a rare and aggressive malignant neoplasm that predominantly affects elderly postmenopausal women and can involve various gynecologic organs. It is characterized by the presence of both malignant epithelial and sarcomatous components. While most uterine carcinosarcomas (UCS) are homologous (sarcomatous component consisting of elements native to the uterus), heterologous components are less common and may vary in composition. Rare heterologous elements can include lipomatous (liposarcoma) or osseous elements (osteosarcoma). We present an unusual case of a 31-year-old female with UCS exhibiting osseous heterologous elements. The patient underwent successful surgical resection and remains in remission during follow-up. This case is notable for its rarity, as highlighted by the uncommon age of the patient and the presence of rare heterologous elements in the UCS. Furthermore, it provides new insights into the diverse presentations of UCS and underscores the importance of comprehensive evaluation in understanding its clinical manifestations.